Meritocratic Labor Income Taxation - Kristoffer Berg; Morten Håvarstein; Magnus E. Stubhaug (Center for Economic Studies and ifo Institute (CESifo), 2024)
Surveys and experiments suggest that people hold workers more responsible for income gains stemming from merit, such as education, than circumstances, such as parental education. This paper shows how to design income taxes that account for merits. First, we introduce social welfare functions that accommodate individual preferences and hold workers responsible for their merits. Second, we show how to map social welfare function primitives into empirically measurable statistics and exploit long-run Norwegian income and family relations register data to examine the relationship between merit and income. Third, we simulate optimal income tax implications of our meritocratic social welfare functions. The result is that accounting for merit leads to lower optimal marginal income tax rates than the utilitarian criterion recommends, but the difference is smaller when workers are not held responsible for merits that are explained by circumstances.
Keywords: D31; D63; H21; 330; equality of opportunity; meritocracy; optimal income taxation; welfare criteria